PD-L1 expression complements CALGB prognostic scoring system in malignant pleural mesothelioma - Avilés-Salas, Alejandro; Cabrera-Miranda, Luis; Hernández-Pedro, Norma; Vargas-Lías, Diana Sofía; Samtani, Suraj; Muñoz-Montaño, Wendy; Motola-Kuba, Daniel; Corrales-Rodríguez, Luis; Martín, Claudio; Cardona, Andrés F.; Palomares-Palomares, Cittim B.; Arrieta, Oscar (Frontiers in Oncology, 2023)
Background Programmed death ligand-1 (PD-L1) expression is a predictive biomarker in patients with lung cancer, but its role in malignant pleural mesothelioma (MPM) remains unclear. Evidence suggests that higher PD-L1 expression is correlated with worse survival. CALGB is the main scoring system used to predict the benefit of chemotherapy treatment. This study aimed to determine the prognostic value of PD-L1 expression and its addition to CALGB scoring system in patients with MPM. Methods In this retrospective analysis, we evaluated samples with confirmed locally advanced or metastatic MPM. PD-L1 Tumor Proportional Score (TPS) was determined by immunohistochemistry at diagnosis. Results 73 patients were included in this study. A cutoff value of 15 was set for a high or low PD-L1 TPS. In total, 71.2% (n=52) and 28.8% (n=21) of individuals harbored low or high PD-L1 expression, respectively. PD-L1High was associated with worse median progression-free Survival (mPFS) [4.9 vs. 10.8 months; HR 2.724, 95% CI (1.44-5.14); p = 0.002] and Overall Survival (OS) [6.0 vs. 20.9 months; HR 6.87, 95% CI (3.4-8.7); p<0.001] compared to patients with PD-L1Low. Multivariate analysis confirmed that PD-L1 expression was an independent factor for PFS and OS in patients with MPM and CALGB score of 5-6. Conclusion PD-L1 addition to CALGB scale improves its prognostic estimation of MPM survival and should be considered in future research.